2015
DOI: 10.1002/2015gc005819
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemical composition, water and temperature on physical properties of continental crust

Abstract: We explore the influence of major elements chemistry and H 2 O-content on the density and seismic velocity of crustal rocks by computing stable and metastable crustal mineralogy and elastic properties as a function of pressure and temperature (P-T). Proposed average compositions of continental crust result in significantly different properties, for example a difference in computed density of $ 4 % is obtained at a given P-T. Phase transformations affect crustal properties at the point that crustal seismic disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 54 publications
2
36
1
Order By: Relevance
“…If, for simplicity, we neglect lateral variations in ρ um and assume a uniform value ranging from 3.30 g/cm 3 for a peridotite model with a warm geotherm [ Afonso et al, ] to 3.38 g/cm 3 from PREM, then our results would imply mean ρ lc of 3.12–3.20 g/cm 3 and 2.9–2.98 g/cm 3 east and west of the RMF, respectively. The western value is consistent with a wide range of felsic and mafic rocks [ Hacker et al, ; Guerri et al, ]. Densities greater than ~3.15–3.2 g/cm 3 east of the RMF would favor mafic compositions [ Hacker et al, ], which may have been emplaced in the lower crust near the time of crust formation or during subsequent magmatic events [e.g., Barnhart et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…If, for simplicity, we neglect lateral variations in ρ um and assume a uniform value ranging from 3.30 g/cm 3 for a peridotite model with a warm geotherm [ Afonso et al, ] to 3.38 g/cm 3 from PREM, then our results would imply mean ρ lc of 3.12–3.20 g/cm 3 and 2.9–2.98 g/cm 3 east and west of the RMF, respectively. The western value is consistent with a wide range of felsic and mafic rocks [ Hacker et al, ; Guerri et al, ]. Densities greater than ~3.15–3.2 g/cm 3 east of the RMF would favor mafic compositions [ Hacker et al, ], which may have been emplaced in the lower crust near the time of crust formation or during subsequent magmatic events [e.g., Barnhart et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the effect of water content, pressure and temperature on the physical properties of crustal rocks cannot be easily addressed by such relationships. Our method has the potential to consider more realistic phase equilibria constraints [Jagoutz and Behn, 2013;Guerri et al, 2015] to better address the effect of composition, water content, Geochemistry, Geophysics, Geosystems 10.1002/2016GC006463 temperature, and pressure on velocity and density of crustal rocks [see, e.g., Afonso et al, 2015]. We expect that this improvement, together with a full 3-D inversion including gravity anomalies and gravity gradients, will help clarify some remaining ambiguities.…”
Section: Discussionmentioning
confidence: 99%
“…These factors tend to reduce V p more than V s , resulting in low bulk V p ∕V s values. The modeling of Ma and Lowry (2017) and Guerri et al (2015) showed that hydration processes can also decreases V p ∕V s values in the crust, except when melt is present. While a recent magnetotelluric study in the SRM (Feucht et al, 2017) does not report a significant reduction in bulk resistivity within the upper crust in this region, felsic materials containing unconnected cracks filled with H 2 O-rich fluids can be an alternative interpretation for the low V p , low V s and low V p ∕V s values observed at shallow depths (≤ 10-15 km) beneath the SRM and southern margins of the CP.…”
Section: P ∕V S Structurementioning
confidence: 99%